1998
DOI: 10.1007/s002940050415
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, sequencing and developmental expression of the genes encoding S4 and S10 ribosomal proteins in the cellular slime mould Dictyostelium discoideum

Abstract: The sequences of the rps4 and rps10 genes encoding the Dictyostelium discoideum homologues of the basic ribosomal proteins S4 and S10 were determined from cDNA and genomic DNA clones. They are expressed respectively as 266 and 153 amino-acid-long proteins. In both cases, the N-terminal methionine is cleaved in the mature proteins. S4 contains two putative nuclear targeting signals and displays a strong overall identity (around 60%) to eukaryotic S4 homologues. The rps10 gene harbours a 314-bp intron located cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…The 870 bp cDNA that rescued cdc24 -2, cdc42 -1 and bem1 was found to encode for the D. discoideum ribosomal protein DdS4. The rescuing DNA constituted a full-length gene with no introns and was identical to the S4 sequence reported in the literature [16]. A messenger RNA encoding D. discoideum S4 was reported to be expressed selectively in prestalk cells [17].…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…The 870 bp cDNA that rescued cdc24 -2, cdc42 -1 and bem1 was found to encode for the D. discoideum ribosomal protein DdS4. The rescuing DNA constituted a full-length gene with no introns and was identical to the S4 sequence reported in the literature [16]. A messenger RNA encoding D. discoideum S4 was reported to be expressed selectively in prestalk cells [17].…”
Section: Resultsmentioning
confidence: 58%
“…Of particular interest to our study, RPL41, a ribosomal large subunit protein, associates with several cytoskeleton components including tubulin β, Y and myosin IIA [43]. In the case of D. discoideum , it has been reported that S4 binds inositol 6-phosphate [16]. The implications remain unknown, but the finding suggests that DdS4 also has a role in the plasma membrane or in signal transduction.…”
Section: Discussionmentioning
confidence: 88%
“…A 32 kDa phosphoprotein (recently identified by Nakao et al as ribosomal protein S6; RPS6) is known to be completely dephosphorylated under conditions of nutritional deprivation: Blockage of the dephosphorylation by phosphatase inhibitors such as okadaic acid and calyculin A completely inhibits differentiation of starving Ax-2 cells from the PS-point so that they advance instead through Mand S-phases to a particular position of the cell cycle (Akiyama and Maeda, 1992). On the other hand, Tapparo et al (1998) have reported that ribosomal protein S4 (RPS4; not mitochondrial RPS4) and S10 (RPS10), both of which are coded by nuclear genome DNA, are expressed at the vegetative growth phase, followed by decrease in response to starvation. Taken together these data offer us indications as to the importance of differential operation of the machinery used for mitochondrial protein synthesis during the transition of cells from growth to differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, there are numerous genes for RPs regulated developmentally in species ranging from D. discoideum to Xenopus and tobacco. RPs studied thus far including S4 and S10 in D. discoideum are known to be developmentally regulated (Ramagopal and Ennis, 1984;Steel and Jacobson, 1987;Tapparo et al, 1998).…”
Section: Variation Of the Expression Level Of The Rpl16a Genementioning
confidence: 99%
“…Those genes are so ubiquitous that almost all eukaryotic organisms may possess such genes. For example, expressions of genes for all ribosomal proteins studied so far are known as being regulated developmentally in Dictyostelium discoideum (Ramagopal and Ennis, 1984;Steel and Jacobson, 1987;Tapparo et al, 1998). In Candida albicans, synthesis of the rp10 transcript is regulated during growth and induced transiently during the transition from the yeast form to the hyphal form (Swoboda et al, 1995).…”
mentioning
confidence: 99%